JUDICIAL SYSTEM AND ITS FORMATION IN BUKHARA EMIRATE (Academicia Globe: Inderscience Research, 2024)
In this article, it is mentioned about the creation and development of the judicial authority in the Bukhara Emirate, the actions of the active judges, and in what cases they are brought to court.